The Ways of Testing the Quality of Inter-Lingual Translation For The Language Leaners - Efendi Barus; Susi Ekalestari (Journal of Applied Linguistics, 2022)
Translation is one of the main aspects in understanding and learning second language. In https://www.gala-global.org said: translation is the communication of meaning from one language (the source) to another language (the target).It is often said as unimportant thing in learning second language or considered as secondary skill. Actually, translation must be supposed as the primary skill for the second language. They must know the meanings of the words or the sentences as a whole. The method of research is on the basis of library research and technical activities done by the undergraduate students. The technique of approach is done in two ways: 1. An approach to the lexical items, 2. An Approach to the Oral and Written Translation. The result of this research is that when one translates text from language A into language B, a different translator then turns the B text back into A, and the resulting A text is compared  with the original A text . If the test is virtually identical, it is strong evidence that the original translation was of high quality. Inter-lingual translation should be a basic skill for mastering L2. The conclusion is that translation, oral or written translation, must be different from those who are already fluent in L2. It must practically be easier the written translation than the oral translation for both, the beginners and the fluent ones. Keywords: Ways of testing, translation, quality L1, L2.